This is rocket science ebook True stories of the risk-taking scientists who figure out ways to explore beyond. - Skurzynski, Gloria (2010)
..three, two, one... we have liftoff! From the award-winning author of Are We Alone? comes a title to propel young imaginations far into space. This Is Rocket Science explores the past, present, and future of space travel. The compelling text--vetted by NASA scientists--is a combination of history, science, human drama, and future challenges. Readers learn how fireworks in ancient China developed into the fire arrows used by Genghis Khan; we meet Sir Isaac Newton, Jules Verne, H.G. Wells, and learn how their imaginations shaped rocketry. We revisit the era of Sputnik, the satellite that launched a superpower space race, ending with moonwalks and a rendezvous in space. Finally we look forward to the future challenges of Mars and beyond. We also get a sneak peek at new technologies like space elevators, solar sails, ion propulsion, and more.